Pertumbuhan Anggrek Hitam pada Simulasi Cekaman Kekeringan Menggunakan Polietilen Glikol secara In Vitro: Black Orchid Growth in Simulated Drought Stress Using Polyethylene Glycol in Vitro - Asnawati Asnawati; Mahmud Mustaqim; Agustina Listiawati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The black orchid plant has a beauty at the flowers with the characteristic black labellum. In its natural habitat, black orchid plants require high humidity for optimal growth. The purpose of this study was to examine the growth response of black orchids to drought stress using polyethylene glycol in vitro. This research was conducted at the Biotechnology Laboratory, Faculty of Agriculture, Tanjungpura University from October to January 2023. The design used in this study was Completely Randomized Design which consisted of one factor, namely polyethylene glycol concentration. The polyethylene glycol concentrations tested were 0%, 5%, 10%, 15%, 20% and 25% (mg/l). The variables observed were the time of shoot emergence, root emergence time, number of shoots, increase in the number of leaves, number of roots, and leaf color morphology. The results showed that the addition of polyethylene glycol at the level of 0-25% in in vitro culture media as a drought stress simulation had no significant effect on the variables of shoot emergence time, root emergence time, number of shoots, increase in number of leaves, and number of roots. Meanwhile, for the morphological variable of leaf color, the treatment with a concentration of 25% showed early symptoms of drought.